2022
DOI: 10.7759/cureus.32324
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Impact of Allergic Rhinitis on Asthma Exacerbations in Asthmatic Adult Patients in the Riyadh Region of Saudi Arabia: A Cross-Sectional Study

Abstract: Objectives: Allergic rhinitis (AR) and asthma are highly prevalent conditions known to occur concomitantly. However, observational, cross-sectional studies in Saudi Arabia assessing the frequency and severity of rhinitis in asthmatics adults using questionnaires based on guidelines are unavailable. Therefore, this study attempted to investigate this side and evaluate the role of triggers, symptoms, and family history or history of AR on asthma control levels.Methods: From April 2nd to September 18th, 2021, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Based on the study by Mahfouz et al, it is noted that patients with AR had a significantly higher risk of experiencing asthma exacerbations compared to those without AR. Over 80% of patients with AR reported experiencing at least one asthma exacerbation in the past year, compared to 72% of patients without AR [ 7 ]. The study conducted by Lababidi et al indicated that the Arabic ACT showed a good correlation with the clinical assessment of asthma control based on Global Initiative for Asthma (GINA) guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the study by Mahfouz et al, it is noted that patients with AR had a significantly higher risk of experiencing asthma exacerbations compared to those without AR. Over 80% of patients with AR reported experiencing at least one asthma exacerbation in the past year, compared to 72% of patients without AR [ 7 ]. The study conducted by Lababidi et al indicated that the Arabic ACT showed a good correlation with the clinical assessment of asthma control based on Global Initiative for Asthma (GINA) guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were asked whether they agreed to participate before filling out the questionnaire. After obtaining permission, we used a questionnaire from a previous study which was taken completely in both languages (Arabic and English) [ 7 ]. It starts first with questions that include and exclude the participants' asthma diagnosis and comorbidity and is composed of the validated Arabic versions of the Score for Allergic Rhinitis (SFAR) questionnaire [ 12 ], Allergic Rhinitis and Its Impact on Asthma (ARIA) Guidelines [ 7 ], and the Asthma Control Test (ACT) questionnaire [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores reflect better asthma control. ACT cutoff points for uncontrolled and partly controlled asthma were ≤19 and ≤22, respectively [ 11 , 12 ]. Respondents whose asthma was reported as controlled or completely controlled were grouped when doing the analysis.…”
Section: Methodsmentioning
confidence: 99%